Penggunaan Media Advanced Puzzle dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran PAI di Sekolah Menengah Pertama - Septiana Purwaningrum; Siti Nunik Khoirul Iftitah (LPTK IAIN Kediri, 2023)
Currently, learning uses a student-centered approach. Teachers are also required to develop their creativity in using strategies, methods or media. On the other hand, students are expected to have 21st century skills known as 4C, namely critical thinking, creativity, collaboration and communication. Critical thinking or critical thinking skills are important to have, so that students are able to think rationally and be able to solve various problems that they face. In fact, students' critical thinking skills are still low. Therefore, the author innovates to make Advanced Puzzle media in order to improve students' critical thinking skills. Media Advanced Puzzle is a learning media in the form of a three-dimensional puzzle that can stimulate students to think critically and be integrated with online material and questions. This learning innovation work was carried out in class VII-I of SMPN 1 Grogol consisting of 32 students. This study aims to find out whether the use of Advanced Puzzle media can improve students' critical thinking skills in PAI learning and how the use of Advanced Puzzle media improves students' critical thinking skills in PAI learning. The results showed that the use of Advanced Puzzle media in PAI learning could improve students' critical thinking skills with an increase of 37.5%. The use of Advanced Puzzle media in improving students' critical thinking skills is through the process of pairing puzzles (which contain material and problems), so that students are able to understand the relationship between material and find solutions to these problems. Sekarang ini, pembelajaran menggunakan pendekatan yang berpusat pada siswa. Guru juga dituntut untuk mengembangkan kreativitasnya dalam menggunakan strategi, metode, atau media. Di sisi lain siswa diharapkan memiliki keterampilan abad 21 yang dikenal dengan istilah 4C yaitu critical thinking, creativity, collaboration dan communication. Kenyataannya, kemampuan berpikir kritis siswa masih rendah. Oleh karena itu, penulis berinovasi membuat media Advanced Puzzle agar dapat meningkatkan kemampuan berpikir kritis siswa. Media Advanced Puzzle adalah media pembelajaran yang berbentuk puzzle tiga dimensi yang dapat memberi stimulus siswa untuk berpikir kritis serta diintegrasikan dengan materi dan soal online. Karya inovasi pembelajaran ini dilaksanakan di kelas VII-I SMPN 1 Grogol yang terdiri 32 siswa. Penelitian ini bertujuan untuk mengetahui apakah penggunaan media Advanced Puzzle dapat meningkatkan kemampuan berpikir kritis siswa pada pembelajaran PAI dan bagaimana penggunaan media Advanced Puzzle dalam meningkatan kemampuan berpikir kritis siswa pada pembelajaran PAI. Hasil penelitian menunjukkan bahwa penggunaan media Advanced Puzzle pada pembelajaran PAI dapat meningkatkan kemampuan berpikir kritis siswa dengan peningkatan sebesar 37,5 %. Penggunaan media Advanced Puzzle dalam meningkatkan kemampuan berpikir kritis siswa yaitu melalui proses memasangkan puzzle (yang berisi materi dan permasalahan), sehingga siswa mampu memahami hubungan antar materi dan menemukan solusi dari permasalahan tersebut.